2019
DOI: 10.1158/1538-7445.am2019-3230
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3230: Safety and efficacy of immune checkpoint inhibitors (ICIs) in patients with HIV, hepatitis B, or hepatitis C viral infections

Abstract: Background: Immune checkpoint inhibitors (ICIs) have become standard of care for many malignancies. However, patients (pts) with human immunodeficiency virus (HIV), hepatitis B (HBV), and hepatitis C (HCV) were excluded from many clinical trials. Therefore, the safety and efficacy of ICI therapy in these patient populations is not well characterized. Methods: We performed a retrospective analysis of pts with HIV, HBV, or HCV treated with ICI therapy at five MedStar Health hospitals from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A total of 21 studies reported ORR data [ 4 , 6 9 , 11 14 , 16 , 18 28 ], involving 815 uninfected patients and 1,061 hepatitis patients. This meta-analysis showed ( Figure 2 ) that the pooled ORR of uninfected patients, HCV patients, and HBV patients was 18.10% (95% CI: 12.00%–25.00%), 23.95% (95% CI: 16.36%–32.28%), and 26.49% (95% CI: 21.12%–32.19%), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 21 studies reported ORR data [ 4 , 6 9 , 11 14 , 16 , 18 28 ], involving 815 uninfected patients and 1,061 hepatitis patients. This meta-analysis showed ( Figure 2 ) that the pooled ORR of uninfected patients, HCV patients, and HBV patients was 18.10% (95% CI: 12.00%–25.00%), 23.95% (95% CI: 16.36%–32.28%), and 26.49% (95% CI: 21.12%–32.19%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of immune-related adverse events (irAEs) in hepatitis patients and uninfected patients was further combined. A total of 13 studies reported irAEs [ 4 , 7 , 8 , 10 12 , 14 , 16 , 18 20 , 22 , 27 ]. irAEs were classified into all grades and grades 3-4.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Shah and colleagues noted in a retrospective analysis of patients who were infected with human immunodeficiency virus (HIV), HBV, or HCV treated with ICI therapy that there was no evidence of viral reactivation. 61 Additionally, previous trials proved no cases of HCV-related flares in cancer patients with positive serology for HCV who had undergone treatment with ICIs. 62,63 Prognosis and Mortality of ICIs-Induced Hepatitis ICIs-induced hepatitis typically improves after treatment with corticosteroids.…”
Section: Ici Treatment In Chronic Viral Hepatitismentioning
confidence: 99%